Representation of Human Qualities in Proverbs and Sayings of Turks of the Middle Ages: Comparative and Historical Analysis - Еskeyeva М.; Аlashbayeva Ж. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
Turkic written records of the middle period is a valuable heritage, which gives information about history, culture and language of Turkic peoples. Detailed study of proverbs of these inscriptions facilitates to define the process of formation and development paramiology of Kazakh language and semantic motivation of proverbs and sayings. This article considers proverbs and sayings of moral standards in the language of Turkic written records of ХІ-ХІІ centuries, as Yusuf Balasaguni‘s “Kutadgu Bilig”, Akhmet Yeguneki’s “Hibatul Hakaiyk” and Akhmet Yassawi’s “Diwani Hikmet”. The author analyzes the ethnocultural content of the proverbs and sayings, describing positive and negative values of person, peculiarities of paroemiological meaning in the framework of semantic field of dominant words of the proverbs and sayings. Furthermore, the author defines similarities and differences of ethno-cultural content the proverbs and sayings of the medieval period written records and modern Kazakh language by comparing them